2012
DOI: 10.1242/bio.20122170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of okadaic acid on cultured clam heart cells: involvement of MAPkinase pathways

Abstract: SummaryOkadaic acid (OA) is one of the main diarrhetic shellfish poisoning toxins and a potent inhibitor of protein phosphatases 1 and 2A. The downstream signal transduction pathways following the protein phosphatase inhibition are still unknown and the results of most of the previous studies are often conflicting. The aim of the present study was to evaluate the effects of OA on heart clam cells and to analyse its possible mechanisms of action by investigating the signal transduction pathways involved in OA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 64 publications
5
11
0
Order By: Relevance
“…However, according to the proteomics analysis, the P. lima exposure significantly changed expression of a great number of proteins, which are potentially involved in multiple physiological processes in mussel, including detoxification, cytoskeleton assembling, metabolism and signal transduction, suggesting the deleterious effects of DSP toxins on P. viridis. In fact, consistent with our results, a growing number of studies have found the genotoxic and cytotoxic effects of OA in bivalves in molecular level (Hanana et al, 2012;Prego-Faraldo et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, according to the proteomics analysis, the P. lima exposure significantly changed expression of a great number of proteins, which are potentially involved in multiple physiological processes in mussel, including detoxification, cytoskeleton assembling, metabolism and signal transduction, suggesting the deleterious effects of DSP toxins on P. viridis. In fact, consistent with our results, a growing number of studies have found the genotoxic and cytotoxic effects of OA in bivalves in molecular level (Hanana et al, 2012;Prego-Faraldo et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Using a mussel cDNA microarray, Manfrin et al (2010) found that 9% of up-regulated transcripts in mussel induced by OA exposure were potentially involved in cytoskeleton organization. Hanana et al (2012) observed that the exposure of clam heart to OA at 1 mM for 24 h could induce disorganization of the actin cytoskeleton, rounding and detachment of the fibroblastic cells.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, protein phosphatase independent effects of DSP toxins are suggested that could possibly be employed to describe human symptomatology that is more likely to be present as a result of sub-acute toxic or at subchronic exposure levels: the latter could also be addressed via functional assays, e.g., cytotoxicity of OA in t lymphocytes (Martin-lopez et al, 2012), caspase-3 independent apoptosis (Hanana et al, 2012;Jayaraj et al, 2009), OA induced neuro-inflammation (Kamat et al, 2012), and granulation of tubulin in cytoplasma of hepatocytes (Rubiolo et al, 2012).…”
Section: Standardized Reference Compoundsmentioning
confidence: 99%